Grain-size control in Ti-48Al-2Cr-2Nb with yttrium additions - Trivedi, P. B.; Patankar, S. N.; Froes, F. H.; Baburaj, E. G.; Genç, A.; Ovecoglu, L. (Springer Science and Business Media LLC, 2002)
A gas-atomized (GA) prealloyed powder of the Ti-48Al-2Cr-2Nb intermetallic and 1.6 wt pct Y were mechanically alloyed (MA) and hot isostatically pressed (hipped) to produce a fully dense nanocrystalline material. Mechanical alloying of the as-blended powder for 16 hours resulted in the formation of a disordered fcc phase. Hipping of the alloy powder produced a single-phase nanocrystalline TiAl intermetallic, containing a distribution of 20 to 35-nm-sized Al2Y4O9 particles. The formation of oxide particles occurred by the chemical combination of Al and Y with oxygen, which entered as a contaminant during milling. Oxide particles increased the hardness of the intermetallic compound and minimized grain growth even at 0.8 Tm, where Tm is the melting point of the compound.